Gender and race in neurotrauma: part 2–underrepresentation in clinical trial enrollment and impact on clinical outcomes - Sue, Tea C.; Churchill, Isabella F.; Parr, Ann M.; Tsai, Eve C. (Frontiers in Neurology, 2025)
The underrepresentation of women and racial minorities in clinical trials populations remains a persistent challenge across many medical specialties, including Neurosurgery. A diverse research cohort brings varied perspectives and experiences, which can lead to more innovative solutions to medical problems, generalizable findings, and the foundations to provide culturally competent care to the populations most affected by the condition at hand. The importance of representative Neurotrauma trial populations cannot be overstated, as results are essential to inform decision making and gender and race have both been shown to significantly influence patient outcomes, as seen in the traumatic brain injury and spinal cord injury populations. Although the path towards gender and racial parity in clinical trial participants has been slow, numerous actions have been taken, including the FDA Safety and Innovation Act (2012) and Omnibus Reform Act (2022) on a systemic level. In this paper, we aimed to explore the barriers to and implications of inadequate representation in neurotrauma trials to outline a roadmap towards more diverse trial inclusion and retention. Key strategies moving forward include recruiting a diverse research team, developing flexible study protocols that support the varying needs of individuals of different backgrounds, establishing methods of data analysis that control for social and demographic factors instead of excluding individuals from participating, introducing patient navigators, reflecting on systemically engrained biases, implementing mandatory reporting of gender and race data, establishing and analyzing policies that keep researchers accountable towards goals of inclusive recruitment, and identifying and addressing unique barriers that individuals at the intersection of gender and racial minority status face.